Asiantuntijoiden näkemyksiä digitalisaation kehittymisen vaikutuksista Venäjän informaatiosodankäyntiin Suomessa - Silander, Kaarle (2025)
Russia launched a large-scale invasion of Ukraine in February 2022. A significant portion of Russia's forces are tied up in Ukraine, so the importance of information warfare and influence operations has increased in Russia's arsenal. Russia aims to shape the information space in western countries to its advantage by using its own narratives.